Analysis of Students' Difficulties in Solving Problems Related to Solid Geometry - Kusuma, Arie Purwa; Aslamia, Arneta Sohobatul; Sintiya, Hani; Rahayu, Retno Ginanjar; Rahmawati, Nurina Kurniasari (S&Co Publishing, 2023)
The aim of this research is to identify the challenges faced by students when solving problems related to solid geometry. The research design employed in this study is descriptive qualitative research. The target population was 23 class VI MI Muhammaduddarain students in the 2022/2023 academic year, who were selected using purposive sampling. The research sample consists of three students who encountered difficulties while solving problems in solid geometry. The selection of research subjects was based on their work, which exhibited the most errors in problem-solving related to solid geometry. Data collection techniques encompassed interviews, tests, and documentation. The research findings indicate that the students encountered various difficulties when solving problems related to solid geometry, including (1) challenges in comprehending the concepts, (2) difficulties in applying principles, and (3) struggles in employing process skills.